2013
DOI: 10.7169/facm/2013.48.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Concerning dense subideals in commutative Banach algebras

Abstract: Abstract. We observe that five polynomial families have all of their zeros on the unit circle. We prove the statements explicitly for four of the polynomial families. The polynomials have coefficients which involve Bernoulli numbers, Euler numbers, and the odd values of the Riemann zeta function. These polynomials are closely related to the Ramanujan polynomials, which were recently introduced by Murty, Smyth and Wang [10]. Our proofs rely upon theorems of Schinzel [13], and Lakatos and Losonczi [9] and some g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Real SR polynomials of height 1 -namely, special cases of Littlewood, Newman and Borwein polynomials -were studied by several authors, see [27][28][29][30][31][32][33][34][35] and references therein 2 . Zeros of the so-called Ramanujan Polynomials and generalizations were analyzed in [37][38][39]. Finally, the Galois theory of PSR polynomials was studied in [40] by Lindstrøm, who showed that any PSR polynomial of degree less than 10 can be solved by radicals.…”
Section: Real Self-reciprocal Polynomialsmentioning
confidence: 99%
“…Real SR polynomials of height 1 -namely, special cases of Littlewood, Newman and Borwein polynomials -were studied by several authors, see [27][28][29][30][31][32][33][34][35] and references therein 2 . Zeros of the so-called Ramanujan Polynomials and generalizations were analyzed in [37][38][39]. Finally, the Galois theory of PSR polynomials was studied in [40] by Lindstrøm, who showed that any PSR polynomial of degree less than 10 can be solved by radicals.…”
Section: Real Self-reciprocal Polynomialsmentioning
confidence: 99%
“…In particular, if the coefficients of P ( z ) are close to a constant, then all its roots lie on the unit circle. For example, let Ej=j![zj](cosh(z))1 denote Euler's numbers; then the polynomial Pn(z)=(1)n0jn(2n2j)E2jE2n2jzj=[wn]1cos(w)cos(wz), is root‐unitary (see ) with non‐negative coefficients. See also for more information and other root‐unitary polynomials.…”
Section: Applications II Non‐normal Limit Lawsmentioning
confidence: 99%